Mathematical Model Used to Compute Packet Energy Consumption-Based Control Topology for WSN - Mohammed Joudah Zaiter; Tariq Mohamed; Abdalrazak Tareq Rahem; Viktar Tsviatkou (Journal of Engineering and Sustainable Development)
Several recent scientific papers have been proposed on power consumption in Wireless Sensor Networks (WSN). Still, the work focused on control topologies of WSN in the field of increasing and prolonging the whole network is limited. This results from their function as routers that send data from edge nodes to the sink. The nodes around the sink node quickly die while delivering much data through intermediate nodes from one node to the sink node. The network lifetime was reduced because the sensor nodes adjacent to the sink consume twice as much power as the others. This problem is not recognized and addressed in more visual detail by the authors. The nodes closest to the sink node will die first. Therefore, this paper proposed a mathematical model to represent packet energy consumption with control topology for WSN. Due to the simulation, more than 90% of sensors are still operational and optimally arranged. The overall battery power remaining in the sensors was greater than 70%.